Bisphosphonates - Bishop, N; Russell, G (Elsevier, 2013)
Over the 40-year period during which bisphosphonates have been used in clinical practice, the mechanism of action for both simple and nitrogen-containing compounds has become clear, although sources variation in individual response still requires further investigation. The additional roles of bisphosphonates beyond osteoclastic inhibition also deserve further study. The targeting of bisphosphonates to bone means that few significant adverse consequences have been identified for the vast majority of those treated. © 2014 Elsevier Inc. All rights reserved.